1996
DOI: 10.1177/0148558x9601100206
|View full text |Cite
|
Sign up to set email alerts
|

The Audit Committee and Earnings Quality

Abstract: This paper provides empirical evidence on the association between audit committee formation and the quality of accounting earnings. The audit committee is responsible for overseeing the jnancial reporting and auditing process of the j r m . This paper assesses the eflectiveness of the audit committee in discharging these responsibilities by comparing the quality, or informativeness, of earnings reports before and after audit committee formation. For this paper, informativeness is measured by the extent to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 18 publications
(7 reference statements)
6
93
3
5
Order By: Relevance
“…Felo, Krishnamurthy andSolieri (2003) find a positive relationship between AC size and financial reporting quality. However, the previous studies indicated that better quality of financial reporting and disclosure leads to improve the performance of the firm (Wild, 1996).…”
Section: Audit Committee Sizementioning
confidence: 96%
See 3 more Smart Citations
“…Felo, Krishnamurthy andSolieri (2003) find a positive relationship between AC size and financial reporting quality. However, the previous studies indicated that better quality of financial reporting and disclosure leads to improve the performance of the firm (Wild, 1996).…”
Section: Audit Committee Sizementioning
confidence: 96%
“…Previous studies find that firms with ACs perform better than those without them and the ACs play a significant role in improving the firm performance (Wild, 1996;Weir, Laing & McKnight, 2002). On contrast, other studies revealed that ACs have no effect on the performance of the firms (Theodorou, 1998;Weir et al, 2002).…”
Section: Audit Committee Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Managers" incentive to exploit accrual basis accounting increases if they are bound to meet specific targets (Holland & Ramsay, 2003;Dechow et al, 1996). Wild (1996) and Dechow et al (1996) suggest that an appropriate monitoring system is essential in controlling the managerial opportunistic behaviour. Thus, the efficiency of such monitoring system shall affect the level of reliability of the accounting data.…”
Section: Earnings Reliability Managerial Opportunism and Corporate Gmentioning
confidence: 99%